1974
DOI: 10.1103/physrevlett.33.528
|View full text |Cite
|
Sign up to set email alerts
|

Raman Detection of One-Phonon—Two-Phonon Interactions in CuCl

Abstract: A large ^-direction dependence of the broad band close to the TO peak is observed and explained qualitatively and quantitatively. The TO peak is found to be repelled out of a two-phonon band by a strong third-order anharmonic interaction.In a crystal having the zinc-blende structure, the first-order Raman scattering allows detection of either the TO(g~0) phonon or the LO(#~0) phonon, according to the selected direction q of the transferred momentum. We have measured at 40 K the scattered intensities of a CuCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…The anharmonic interactions result in a shift and broadening of the TO mode and a transfer of oscillator strength to the two-phonon Raman scattering [2,6]. The strength of the anharmonic coupling is determined by Fourier coefficients of the third derivatives of the lattice potential with respect to atomic displacements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anharmonic interactions result in a shift and broadening of the TO mode and a transfer of oscillator strength to the two-phonon Raman scattering [2,6]. The strength of the anharmonic coupling is determined by Fourier coefficients of the third derivatives of the lattice potential with respect to atomic displacements.…”
Section: Resultsmentioning
confidence: 99%
“…Instead of narrow Raman lines corresponding to the characteristic transverse (TO) and longitudinal (LO) optical modes of zincblende crystals, CuCl shows, in the region of the TO mode frequency, a broad structure consisting of three maxima with TO-like polarization characteristics. There exist two different explanations for the anomalous TO structure, the Fermi-resonance model (FRM) [2,6] and the off-center model (OCM) [7,8]. The FRM assumes a strong anharmonic coupling of the bare TO phonon with acoustic twophonon states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, according to Phillip's criterion for ionicity 13 , CuCl is just outside the rocksalt stability range. Many properties of CuCl suggest strong anharmonicity: negative thermal expansion 14 , negative Grüneisen parameters 14,15 , unusual and broad Raman peaks [16][17][18] , asymmetric phonon line shapes 19 and a rich phase diagram 20,21 . Slack and Andersson 12 measured κ(P) of CuCl and found very low κ (< 1W/m-K at room temperature (RT)) that decreased with increasing P. This pressure response is unusual, though found in a few other systems 12,[22][23][24] , and was attributed to large negative Grüneisen parameters of transverse acoustic (TA) modes.…”
mentioning
confidence: 99%
“…However, this quasiparticle approach must be modified whenever accidental degeneracies occur between quasiharmonic phonons and singularities in the two-phonon density of states (DOS). Prior work has found that the line-shapes of the TO(Γ) Raman peaks in GaP, [2,3] CuCl, [4,5] and ZnS [6,7] are profoundly altered by resonant mixing between the TO(Γ) mode and Brillouin Zone boundary (ZB) TA + LA combinations. In fact, this mixing is sufficiently large in CuCl and ZnS at room temperature (RT) and 1 atm.…”
Section: Introductionmentioning
confidence: 99%